Ranking of railway construction project delay factors in Malaysia by using relative importance index (RII) - Ramli M.Z.; Abidin M.Z.Z.; Hamid N.B.; Razman R.; Noh N.A.M. (American Institute of Physics Inc., 2023)
Delay is a critical and common issues to the contractor, consultant or client in every construction project from all over the world. Negative impacts from the construction delay can affect the organization itself. In this era, rail transportation is one of the famous transportations in Malaysia apart from the road transportation and air transportation. Railway construction is one of the constructions which is active in Malaysia. Basically, when the railway construction project faced the delay matter, the organization will encounter the cost overrun and time overrun. From the previous studies, there are many researchers mentioned about the causes and impacts of the railway construction in Malaysia. However, the investigation has not been extensively studied to reduce this phenomenon. In this study, the delay factors involved for railway projects in Malaysia has been determined and ranked. The questionnaire was distributed to 30 experts for validation of the delay factors obtained from literature. The questionnaire survey was divided into 3 sections which the first section was demographic question, second section was the delay factors and lastly the impact of the delay. Meanwhile, the second level of questionnaire was distributed to 118 respondents who are involved in railway construction project. There were fifty-seven delay factors extracted from previous studies with a total of seven groups. To rank these delay factors, Relative Important Index (RII) method was used based on the first and second level of questionnaire data. Thus, at the end of this study, the most significant delay factors from first level questionnaire data are (1) political scenario; (2) mistakes / discrepancies in contract documents; (3) shortage of materials; (4) design changes and (5) financial problems. From the second level of questionnaire data, the most significant delay factors are (1) delay in material procurement; (2) low quality of materials; (3) unforeseen ground condition; (4) accident/safety and health issues during construction; and (5) delay payment to sub-contractor. 2021 American Institute of Physics Inc.. All rights reserved.